2007
DOI: 10.1016/j.acn.2007.01.022
|View full text |Cite
|
Sign up to set email alerts
|

Trail Making Test in traumatic brain injury, schizophrenia, and normal ageing: Sample comparisons and normative data

Abstract: The Trail Making Test (TMT) has been a useful assessment tool to investigate executive function. Several studies have recently improved the existing TMT norms by mean of large samples of healthy individuals stratified by a number of demographic variables from different populations. In contrast, criticisms have been raised about the utility of norms from healthy samples to detect changes across time in clinical samples where TMT performance used to be altered. In addition, few studies have compared groups of pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

17
120
0
4

Year Published

2009
2009
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(141 citation statements)
references
References 61 publications
17
120
0
4
Order By: Relevance
“…The fact that numerous studies report additional effects of aging specific to performance in the alternating condition of the TMT (see for example: Rasmusson et al, 1998;Periáñez et al, 2007) is likely to reflect the additional motor demands required for the completion of the TMT, decreased motor speed being significantly associated with increased age (see for example, Seidler et al, 2010) and poorer performance in tests of long-term memory (Rönnberg, 1990). Further evidence for the influence of spatial characteristics of the TMT on test performance can be seen by comparing the mean relative difference in performance in the TMT-A and B when the spatial characteristics of the test have and have not been controlled for.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that numerous studies report additional effects of aging specific to performance in the alternating condition of the TMT (see for example: Rasmusson et al, 1998;Periáñez et al, 2007) is likely to reflect the additional motor demands required for the completion of the TMT, decreased motor speed being significantly associated with increased age (see for example, Seidler et al, 2010) and poorer performance in tests of long-term memory (Rönnberg, 1990). Further evidence for the influence of spatial characteristics of the TMT on test performance can be seen by comparing the mean relative difference in performance in the TMT-A and B when the spatial characteristics of the test have and have not been controlled for.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have examined how age affects the time to complete both the TMT-A and TMT-B and in adults have shown that the time necessary to complete the TMT increases with age (Periáñez et al, 2007;Tombaugh, 2004;Giovagnoli et al, 1996). In contrast, conclusions regarding the influence of education level on TMT performance have been inconsistent.…”
Section: Introductionmentioning
confidence: 98%
“…In contrast, conclusions regarding the influence of education level on TMT performance have been inconsistent. Some studies have shown that education level affects both parts of the TMT (Periáñez et al, 2007;Giovagnoli et al 1996;Stuss, Stethem, & Poirier, 1987), with the time necessary to complete the TMT-A and TMT-B being shorter for persons with a higher education level. However, other studies have found that education level affects only the TMT-B (Tombaugh, 2004;Hashimoto et al, 2006;Ivnik, Malec, Smith, Tanglos, & Petersen, 1996).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[11][12][13] There are declines in both TMT A and B performance in ageing. 10,[14][15][16][17][18][19][20] There is also evidence for performance deficits on TMT B in mood disorders 21 and in patients with schizophrenia and their relatives 18,[22][23][24][25][26][27] Family-based and twin-based studies have provided evidence for a genetic contribution to individual differences in trail making, estimating the heritability for trail making part A between 0.23 and 0.38, and between 0.39 and 0.65 for trail making part B. [28][29][30] A recent genome-wide association study (GWAS) of trail making part A and part B in a sample of around 6000 individuals did not find any genome-wide significant hits; 31 however, GWAS of other cognitive phenotypes have demonstrated that much larger sample sizes are required to reliably identify significant genetic loci.…”
Section: Introductionmentioning
confidence: 99%